Estimation of Dual Polarization Weather Radar Variables - Dalia A. Mahmood (Al-Mustansiriyah Journal of Science)
Dual polarization weather radar has now become a widely used as instrument in meteorological offices around the world because of its capability in distinguishing different precipitation type and in improving the accuracy of quantitative precipitation estimation. The aim of this work is to estimate the polarimetry radar variables for radars of different frequency bands and study their behavior with rainfall rates. Calculations of polarimetry radar variables were made on the basis of several assumptions. The results showed that factors at horizontal and vertical polarization, ZH,V, ranges between 20 dBz respectively, and more than 55 dBz for light rain and extreme heavy rain respectively, and radar reflectivity factor at horizontal ZH is greater than radar reflectivity factor at vertical ZV for all rainfall rates. The differential reflectivity, ZDR, also increases with increasing rainfall rates since it is the difference between ZH and Zv. Calculations of specific differential attenuation indicated that X band radars are seriously atten-uated by rain and C band radars are less affected by rain. The specific differential attenuation, S band radars is very small. In addition to this feature, the results showed that the differential phase shift between return signals of horizontal and vertical polarizations for S band radars is much less than those for C and X band radars, and also, the results showed that the co-polarization correlation coefficient for S band the radars is much higher than those of C and X bands. In order to investigate the accuracy of the calculated polarimetric weather radar variables per-formed in this research, real radar measurements were used for this purpose. Results indicated that the range of values for calculated polarimetric radar variables are very consistent with range of values for measured variables